Effects of iodine status on thyroid volume and goiter in children living in an iodine-replete area - Yun Jeong Lee; Young Hun Choi; Youn-Hee Lim; Bung-Nyun Kim; Johanna Inhyang Kim; Yun-Chul Hong; Young Joo Park; Choong Ho Shin; Sun Wook Cho; Young Ah Lee (European Thyroid Journal, 2023)
Objective: Adequate iodine intake is essential for growing children, and thyroid volume (Tvol) is considered as an indicator of iodine status. We investigated Tvol and goiter using ultrasonography (US) and their association with iodine status in 228 6-year-old children living in Korea. Methods: Iodine status was assessed using urine iodine concentration (UIC) and categorized as deficient (<100 μg/L), adequate (100–299 μg/L), mild excess (300–499 μg/L), moderate excess (500–999 μg/L), and severe excess (≥1000 μg/L). Tvol was measured using US, and a goiter on the US (goiter-US) was defined as Tvol greater than 97th percentile value by age- and body surface area (BSA)- specific international references. Results: The median Tvol was 2.4 mL, larger than the international reference value (1.6 mL). The age- and BSA-specific goiter-US rates were 25.9% (n = 59) and 34.6% (n = 79), respectively. The prevalence of excess iodine was 73.7% (n = 168). As iodine status increased from adequate to severe excess, the goiter-US rate significantly increased (P for trend <0.05). The moderate and severe iodine excess groups showed higher risk of goiter-US (adjusted odds ratio (aOR) = 3.1 (95% CI: 1.1–9.2) and aOR = 3.1 (95% CI: 1.2–8.3), respectively; age-specific criteria) than the iodine-adequate group. Conclusions: Excess iodine was prevalent in Korean children, and their Tvol was higher than the international reference values. Goiter rate was associated with iodine excess, which significantly increased in the moderate and severe iodine excess groups. Further studies are warranted to define optimal iodine intake in children.